The giant-slayer - Lawrence, Iain, 1955- (Yearling, 2012)
When her eight-year-old neighbor is stricken with polio in 1955, eleven-year-old Laurie discovers that there is power in her imagination as she weaves a story during her visits with him and other patients confined to iron lung machines.